The Application of Yi Musical Elements in the Composition of Contemporary Chinese Pipa Music Case Study "Yi Dance Music" and "Torch Festival Night" - Yeye, Li (Journal of Roi Kaensarn Academi, 2024)
The Pipa is the king of plucking music in Chinese national musical instruments. Since the introduction of the Silk Road into China, its development has an inseparable source of blood with minority music. With the deepening of research on the style and regional characteristics of ethnic minorities, more and more works of ethnic minority Pipa emerge. Among them, the works of Yi people play an important role in the creation of minority Pipa music. This article tries to explain how the Yi music elements are used in the creation of contemporary Chinese Pipa music by introducing the historical origin of the minority culture and the art of the pipa, the musical features of the Yi nationality, the analysis of the use of the musical materials of the Yi people and the characteristics of the musical structure.